TheStrategic Proposals to Develop Learning Person Competency in the Digital Erafor Administrators ofOpportunity Expansion School Under Khonkaen Primary Educational ServiceAreaOffice5 - Phunorn, Krittrin; Thawinkarn, Dawruwan (Journal of Education Rajabhat Maha Sarakham University, 2021)
The purpose of this research was to create and validate a strategic proposal to develop learning person competency in the digital era for administrators of opportunity expansion schools under KhonKaen Primary Educational Service Area Office 5. The research methodology was conducted in 2 phases: 1) reviewing related literature and conducting in-depth interviews with the5 selected experts. 2) examination of proposed strategy offered bythe5 experts to assess the propriety, feasibility, and utility of the strategic proposal. The results found that: the strategic proposals to developing learning person competency in the digital era for administrators of opportunity expansion school under KhonKaen Primary Educational Service Area Office 5 were consisted of6aspects: (1) vision with 1 recommendation (2) mission with 1 recommendation (3) goal with 3 recommendations (4) objective with 1 recommendation (5) strategic with 3 recommendations (6) practices with 6 recommendations on learning person competency in the digital era include learning behavior, using of digital media, thinking skill, decision-making and problem solving, and being a professional administrator. Findings from the strategic proposal review results of the propriety ( = 4.51), the feasibility ( = 4.52), and the utility ( = 4.81) which was at the highest level.